Services of general interest information on iTV a personalised and dynamic approach - Campelo, D. (2018)
This paper aims to present an ongoing PhD research project in Information and Communication in Digital Platforms course of University of Aveiro and University of Porto. This study, which started in June/2016 and is 24 months long, aims to study, conceptualize, prototype and validate a system for personalized and dynamic recommendation of informative videos about public and social services, for later exhibition on an Interactive TV platform (iTV). The target audience of this study are the Portuguese seniors and this project expects to enrich the television experience, to contribute to enhance seniors' information levels and, consequently, enable higher levels of satisfaction, autonomy and quality of life.